(untitled) (Homoeopathy for All, 2024)
Gangrene is one of the serious complications found mostly in people who have diabetes or blood vessel disease. Multidisciplinary management of gangrene is necessary to avoid complications like amputation and permanent disability. Homoeopathy can prevent amputation in such condition by stimulating the immune response of the body. It helps in healing of wound by increasing the blood circulation of the affected area, it is evident from this case of male with age of 55 years who was suffering from gangrene and treated within 4 months with Homoeopathic similimum which was selected on the basis of individualisation.